2012
DOI: 10.1097/igc.0b013e318234f852
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Human Epididymal Protein 4, Cancer Antigen 125, and Risk for Malignancy Algorithm in Ovarian Cancer and Endometriosis

Abstract: HE4 showed satisfactory capability of distinguishing endometriosis from ovarian cancer, which CA125 lacked. The Risk of Ovarian Malignancy Algorithm score proved to be useful in excluding malignant diagnosis in premenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Overall, ultrasound diagnosis of ovarian masses with increased HE4 and CA-125 suggests the presence of ovarian cancer; if only increased CA-125 is observed, the patient may have ovarian endometriosis or other benign diseases; if only increased HE4 is observed, the patient may have ovarian or endometrial cancer or other malignant tumors. Consistent with results of Chinese and worldwide studies (Moore et al, 2011;Bandiera et al, 2011;Jacob et al, 2011;Lenhard et al, 2011;Montagnana et al, 2011;Van Gorp et al, 2011;Kadija et al, 2012), our retrospective analysis showed that HE4 can be used as a marker for the diagnosis of ovarian cancer and endometrial cancer, and is more effective than using CA-125.…”
Section: Comparison Of Ca-125 Among Groupssupporting
confidence: 78%
“…Overall, ultrasound diagnosis of ovarian masses with increased HE4 and CA-125 suggests the presence of ovarian cancer; if only increased CA-125 is observed, the patient may have ovarian endometriosis or other benign diseases; if only increased HE4 is observed, the patient may have ovarian or endometrial cancer or other malignant tumors. Consistent with results of Chinese and worldwide studies (Moore et al, 2011;Bandiera et al, 2011;Jacob et al, 2011;Lenhard et al, 2011;Montagnana et al, 2011;Van Gorp et al, 2011;Kadija et al, 2012), our retrospective analysis showed that HE4 can be used as a marker for the diagnosis of ovarian cancer and endometrial cancer, and is more effective than using CA-125.…”
Section: Comparison Of Ca-125 Among Groupssupporting
confidence: 78%
“…Thus, the overall view is that for women who are not at clearly high risk for ovarian cancer, the "harms" of routine screening for ovarian cancer outweigh the benefits [16]. Although the possibility of employing biomarkers other than CA-125 has been examined [17][18][19][20][21], none of these appear to sufficiently improve diagnostic accuracy to recommend their use for routine ovarian cancer screening [22].…”
Section: The Clinical Problem: the Need For Accurate And Timely Detecmentioning
confidence: 99%
“…Currently, several trials are under way using test kits from various manufacturers [13,14,16,19,21,22]. The strategy with ROMA, as well as normal ranges, cutoff points, and interpretation await further optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Modern imaging techniques and fast progress in laboratory tests have enabled a great step forward in diagnostic algorithms [4][5][6][7][8][9][10][11]. ROMA (Risk of Malignancy Algorithm) based on CA125 and the novel HE4 marker has recently emerged as a promising approach to the preoperative categorization of malignancy risk [12][13][14][15][16][17][18][19][20][21][22]. HE 4 is new marker which was recently proposed for ovarian cancer because of its specificity and high expression in ovarian cancer tissues [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%